2009
DOI: 10.1378/chest.08-2209
|View full text |Cite
|
Sign up to set email alerts
|

Serum Surfactant Protein-A Is a Strong Predictor of Early Mortality in Idiopathic Pulmonary Fibrosis

Abstract: Increased serum SP-A level is a strong and independent predictor of early mortality among patients with IPF. A prediction model containing SP-A and SP-D was substantially superior to a model with clinical predictors alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(126 citation statements)
references
References 26 publications
(42 reference statements)
3
121
0
2
Order By: Relevance
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…In a group of seven asymptomatic patients with signs of early pulmonary fibrosis in the posterior subpleural region on CT scanning, increased levels of serum SP-A and SP-D were detected [44] Kinder et al found that high levels of SP-A at time of initial diagnosis was a strong predictor of mortality in a well defined group of 82 patients with IPF. Furthermore, a model using baseline serum SP-A and SP-D provided substantial additive predictive value and was superior to a model based on clinical parameters alone [45].…”
Section: Kl-6mentioning
confidence: 92%
“…They have also been shown to have prognostic value for mortality in IPF; concentrations of SP-A may indicate a more destructive phenotype, and concentrations of SP-D appear to relate to the extent of deterioration in pulmonary function per year and the degree of radiographic abnormality. [45][46][47][48] Kinder and colleagues 46 demonstrated that the addition of SP-A and SP-D to an IPF clinical prediction model improved performance in the prediction of 1-year mortality.…”
Section: Sp-a and Sp-dmentioning
confidence: 99%
“…Assessment of COPD exacerbations relies mostly on clinical 43,44,[58][59][60] ; MMP 5 matrix metalloproteinase 11,40,[49][50][51]53 ; MPIF-1 5 myeloid progenitor inhibitory factor-1 61 ; S100A12 53 ; SP 5 surfactant protein 10,[34][35][36][37]46,48,62,[58][59][60] ; TNF-a 5 tumor necrosis factor-a 10,26 ; TNFRSF1A 5 tumor necrosis factor receptor superfam ily, member 1A 51 ; VCAM-1 5 vascular cell adhesion moledule-1 53 ; YKL-40. 56 to identify clinical phenotypes such as rapid decliners and frequent exacerbators.…”
Section: Biomarkers Of Copd and Ipf Exacerbationsmentioning
confidence: 99%